2007
DOI: 10.3892/ijo.31.3.567
|View full text |Cite
|
Sign up to set email alerts
|

The combination of the histone-deacetylase inhibitor trichostatin A and gemcitabine induces inhibition of proliferation and increased apoptosis in pancreatic carcinoma cells

Abstract: Abstract. The prognosis of advanced pancreatic cancer is poor. Established chemotherapy shows only limited efficacy and significant side effects. We investigated how far a combination of trichostatin A (TSA) and gemcitabine synergizes to inhibit proliferation and promotion of apoptosis of pancreatic adenocarcinoma cells in vitro. The human pancreatic carcinoma cells YAPC, DANG and Panc-89 and primary human foreskin fibroblasts as non-malignant controls were cultured under standardized conditions and incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Caspase-3 is one of the most important executioners which is capable of cleaving many important cellular substrates, and caspase-3 mediated cell death plays an important role in pathogenesis and therapy of a variety of cancers (31,32). Our results found that disruption of Δ"m and activation of caspase-3 was highly correlated with CGZ-induced apoptosis in NB4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is one of the most important executioners which is capable of cleaving many important cellular substrates, and caspase-3 mediated cell death plays an important role in pathogenesis and therapy of a variety of cancers (31,32). Our results found that disruption of Δ"m and activation of caspase-3 was highly correlated with CGZ-induced apoptosis in NB4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although preclinical data suggests that antagomiRs or miRNA replacement therapy is promising for pancreatic cancer models, clinical use is hampered by unresolved drug delivery and the fact that one miRNA also has several target mRNAs, thus possibly being too unspecifi c [ 184 , 185 ]. Overall, as most of the agents highlighted above are currently in early phases of clinical development, no clear data on effi cacy of epigenetic agents in pancreatic cancer are available, but promising preclinical [ 186 ] and early clinical data warrant further development.…”
Section: Potential Targets For Epigenetic Therapy In Pancreatic Cancermentioning
confidence: 99%
“…/CDKN1A, and regulators of cell survival/death are involved in the mediation of antiproliferative and proapoptotic effects of HDACI [13][14][15]17] . The molecular basis of variations in the biological efficiency of HDACI in different PC cells, however, has not been systematically studied so far.…”
Section: Waf1mentioning
confidence: 99%
“…With respect to PC, recent experimental studies have suggested that HDACI may efficiently inhibit growth and induce apoptosis even of drug resistant cell lines [13][14][15] . Furthermore, a synergistic action with classic cytostatic drugs, such as gemcitabine, has been demonstrated [16][17][18] . We have recently shown that HDACI also exert antifibrotic efficiency by inhibiting functions of pancreatic stellate cells [19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation